(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical characteristics and associated factors in patients with Candida onychomycosis. Subjects and methods: A cross-sectional descriptive study was conducted on 76 patients diagnosed with onychomycosis who were examined and treated at the National Hospital of Dermatology and Venereology from January 2025 to July 2025. Epidemiological characteristics, related behaviors, underlying comorbidities, and clinical manifestations were collected and analyzed. Isolation and identification of Candida species were performed according to routine mycological laboratory procedures. Associations between clinical factors and the extent of nail involvement were assessed using appropriate statistical tests. Results: Among the 76 patients with onychomycosis, 39 cases were confirmed as Candida infections, accounting for 51.32%. The condition was more prevalent in females (69.23%) and in patients older than 40 years (66.67%). A higher proportion of patients resided in rural areas compared with urban areas. Candida onychomycosis was commonly associated with inappropriate hand and foot hygiene practices, particularly frequent exposure to water and detergents. Statistical analysis demonstrated significant associations between disease duration, inappropriate use of cleaning agents, and diabetes mellitus with the number of affected nails. In addition, disease duration was significantly associated with the presence of subjective symptoms such as pruritus, pain, and periungual inflammation. Conclusions: Prolonged disease duration and diabetes mellitus are closely associated with the extent of nail involvement in patients with Candida onychomycosis. Disease duration also influences clinical manifestations, including pruritus, pain, and periungual inflammation.